Analysis of Problems and Countermeasures of Artificial Intelligence in Business Analytics - Chen, Weiye (Transactions on Economics, Business and Management Research, 2024)
The use of Artificial Intelligence (AI) in business analytics presents significant opportunities and challenges. This study analyzes the major issues in AI implementation, such as data accuracy, high initial cost, and privacy protection. To address these issues, the study proposes countermeasures, including strengthening data governance, reducing initial costs through cloud-based AI services, and enhancing data privacy protection measures. The results of the study point out the specific manifestations and solutions to these problems and provide actionable strategic recommendations for enterprises in AI applications. This study has significant application value for how enterprises can improve decision-making efficiency, reduce operational risks, and achieve sustainable development through AI.